Method for preparing ultra-pure nano copper powder through reduction of organic copper salt
By using high-purity organic copper salts and gaseous reducing agents in supercritical carbon dioxide, the problems of solvent residues and metal impurities are solved, and the preparation of nano-copper powder with high purity and high performance is achieved.
Patent Information
- Application Number
- CN202411656880.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
When preparing nanocopper powder with existing chemical reduction methods, a large amount of liquid solvent is required, resulting in solvent residue, reducing the low-temperature sintering performance and conductivity of nanocopper powder. At the same time, the supercritical carbon dioxide microemulsion method introduces metal impurities, resulting in a low purity of nanocopper powder. and surface oxidation.
In supercritical carbon dioxide solvents, high-purity organic copper salts and gaseous reducing agents are used as reactants to avoid the addition of surfactants and water, and directly react in supercritical carbon dioxide to overcome the problems of solvent residues and metal impurities introduction.
The preparation of solvent-free residue and high-purity nanocopper powder is achieved, the surface oxidation of nanocopper powder is avoided, and its conductive properties and low-temperature sintering properties are improved. It is suitable for conductive inks and electrical and electronic fields.
Smart Images

Figure CN119457044A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ultrapure nano-copper preparation technology, and in particular to a method for preparing ultrapure nano-copper powder by reduction of organic copper salts. Background Technology
[0002] Due to its excellent properties such as good ductility, high conductivity, and large specific surface area, nano-copper powder has significant application prospects in many fields such as lubrication, conductive inks, and electrical and electronic engineering. Preparation methods for nano-copper powder can be categorized into mechanical grinding, evaporation and condensation, laser high-temperature ablation, chemical reduction, microemulsion, sol-gel, and electrochemical methods. Chemical reduction is widely used due to its advantages of simple equipment, good controllability, and low cost. However, conventional chemical reduction methods use large amounts of liquid solvents. For example, Chinese patent CN 101890506A discloses a method for preparing nano-copper particles, using liquid paraffin as a solvent and reducing agent to synthesize copper nanoparticles. The product needs to be washed alternately with petroleum ether, distilled water, and anhydrous ethanol to remove organic solvents and stabilizers. Another example is Chinese patent CN102371358A, which discloses an aqueous phase preparation method for redispersible nano-copper particles, using water or a mixture of water and organic solvents as solvents, and preparing nano-copper particles under the action of ammonia and a reducing agent. Conventional chemical methods require complex methods to remove the liquid solvents used, and their residues significantly reduce the low-temperature sintering performance of copper nanoparticles, severely affecting the conductivity of the sintered products and negatively impacting their application in conductive inks, electrical and electronic fields. Therefore, there is a need to develop a chemical method for preparing copper nanoparticles that does not use liquid solvents.
[0003] In recent years, supercritical hydrothermal synthesis of nanomaterials has emerged. The preparation of nano-copper typically involves the rapid saturation precipitation of copper salts and their oxides in supercritical water, followed by subsequent reactions, to obtain ultrafine powders. However, the presence of water easily leads to surface oxidation of the nanoparticles. Using supercritical carbon dioxide can avoid this problem. However, if supercritical carbon dioxide is used as a solvent, highly polar copper salts such as copper nitrate and copper chloride are difficult to dissolve directly in supercritical carbon dioxide, requiring the use of a microemulsion method. Due to the increased number of components, the complexity of microemulsion preparation increases dramatically. Most importantly, the microemulsion method requires: 1. the use of surfactants (such as fluorosulfonates) and reducing salts (such as sodium borohydride), often introducing other metal ions (sodium ions, potassium ions, etc.), resulting in low purity of the produced nano-copper powder; 2. the introduction of an aqueous phase other than the oil phase (supercritical carbon dioxide) to obtain the emulsion, which causes surface oxidation of the nano-copper powder, hindering its low-temperature sintering; and 3. the presence of residual conventional reducing agents or their reduction products at room temperature and pressure. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing ultrapure nano-copper powder by reduction of organic copper salts. Using high-purity organic copper salts and a gaseous reducing agent in a supercritical carbon dioxide solvent as reactants, this method eliminates the need for surfactants and water to form a microemulsion. It overcomes the problems of liquid solvent residues required in previous preparation methods, and the metal ion inclusions caused by the supercritical carbon dioxide microemulsion method, resulting in low purity and surface oxidation of the nano-copper powder.
[0005] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted:
[0006] This invention provides a method for preparing ultrapure nano-copper powder by reduction of organic copper salts, comprising the following steps:
[0007] (1) Place the organic copper salt and morphology control agent in a container, add the dehydrating agent, introduce the gas reducing agent, introduce carbon dioxide and adjust the carbon dioxide pressure and temperature to make the carbon dioxide reach the supercritical state, stir, and obtain a mixture.
[0008] (2) The mixture obtained in step (1) is heated to react and the reaction product is obtained (morphology control agents such as PVP will help copper particles to be dispersed in supercritical carbon dioxide in the form of colloidal particles). The mixture is cooled and depressurized (copper particles coated with morphology control agents are precipitated), excess morphology control agents and organic products are washed away, and ultrapure nano copper powder is obtained after drying.
[0009] The following is a detailed explanation:
[0010] Step (1):
[0011] In some embodiments, the organic copper salt is one or more selected from copper fatty acids, copper naphthenates, and copper oleate with a carbon chain length of 8-18 carbons; the purity of the organic copper salt is ≥5N (99.999%).
[0012] In some embodiments, the morphology control agent is one or more selected from polyvinylpyrrolidone (PVP), hexadecyltrimethylammonium bromide, and chitosan, preferably with an average molecular weight of 10,000-58,000 g / mol for PVP and an average molecular weight of 10,000-50,000 g / mol for chitosan.
[0013] A morphology control agent is added to in-situ coat the subsequently prepared nano-copper powder to obtain near-spherical particles.
[0014] In some embodiments, the mass ratio of the organic copper salt to the morphology control agent, based on copper element, is 1:20 to 1:100.
[0015] In some embodiments, the dehydrating agent is one of 3A or 4A molecular sieves, preferably 3A molecular sieve.
[0016] In some embodiments, the mass ratio of organic copper salt to dehydrating agent is 1:4 to 1:20, based on copper element.
[0017] In some embodiments, the gaseous reducing agent is one or more selected from hydrogen, formaldehyde, and carbon monoxide, preferably hydrogen. The pressure of the introduced gaseous reducing agent is 0.2 MPa-1.0 MPa.
[0018] In some implementations, the molar ratio of the organic copper salt to the gaseous reducing agent, based on copper element, is less than 1:50.
[0019] In some implementations, the pressure of the introduced carbon dioxide is 8-20 MPa and the temperature is 40-80°C.
[0020] In some implementations, the mass ratio of carbon dioxide to organic copper salt, based on copper element, is higher than 900:1.
[0021] In some implementations, stirring is performed for 10-60 minutes.
[0022] Step (2):
[0023] In some implementations, the heating temperature is 160-220°C and the reaction time is 0.5-4 hours.
[0024] The obtained ultrapure nano copper powder has an average particle size of less than 100 nm and a metal-based purity (the proportion of copper element in the total mass of metal elements in the nano copper powder) of ≥99.997%, making it suitable for conductive inks, PCB sintering copper pastes, and other fields.
[0025] Beneficial effects:
[0026] 1. This invention uses organic copper salt as the copper source, which can be directly dissolved in supercritical carbon dioxide solvent without the need for surfactants and water, thus avoiding the introduction of other metal impurities or surface oxidation into the nano copper powder product, and can prepare ultrapure nano copper powder.
[0027] 2. This invention uses a gaseous reducing agent, leaving no residue after preparation. At the same time, by avoiding surfactants, it simplifies subsequent cleaning and purification steps, which is beneficial for obtaining ultrapure nano copper powder.
[0028] 3. This invention removes trace amounts of water generated during the reaction by adding a dehydrating agent in situ, thus protecting the nano-copper powder from oxidation.
[0029] The present invention has been described in detail above; however, the above embodiments are merely illustrative in nature and are not intended to limit the invention. Furthermore, this document is not limited to the foregoing prior art or the invention itself, or to any theory described in the following embodiments. Attached Figure Description
[0030] Figure 1 Here is a scanning electron microscope image of the ultrapure copper nanoparticles obtained in Example 1;
[0031] Figure 2 The image shows the laser particle size distribution of the ultrapure copper nanoparticles obtained in Example 1.
[0032] Figure 3 The X-ray diffraction pattern of the ultrapure copper nanopowder obtained in Example 1;
[0033] Figure 4 The image shows the laser particle size distribution of the ultrapure copper nanoparticles obtained in Example 2.
[0034] Figure 5 The image shows the laser particle size distribution of the ultrapure copper nanoparticles obtained in Example 3.
[0035] Figure 6 The image shows the laser particle size distribution of the ultrapure copper nanoparticles obtained in Example 4.
[0036] Figure 7 The X-ray diffraction pattern of the ultrapure copper nanoparticles obtained in Comparative Example 1 is shown. Detailed Implementation
[0037] The present invention will be further described below with reference to the embodiments. It should be noted that the following embodiments are provided for illustrative purposes only and do not constitute a limitation on the scope of protection of the present invention.
[0038] Unless otherwise specified, the raw materials, reagents, and methods used in the embodiments are all conventional raw materials, reagents, and methods in the art.
[0039] Example 1
[0040] 0.2 g of copper stearate (5N, 99.999%) and 0.4 g of polyvinylpyrrolidone (PVP, average molecular weight 10000 g / mol) (4N, 99.99%) were placed in a 100 ml high-pressure vessel. 0.1 g of 3A molecular sieve was added, and high-purity hydrogen gas (copper:hydrogen molar ratio = 1:56.3) was introduced at 0.4 MPa. The partial pressure of carbon dioxide and the temperature were adjusted to 10 MPa and 40 °C, respectively. The mixture was stirred for 60 min. The temperature was then raised to 180 °C and reacted for 2 h. Subsequently, the temperature was lowered and the pressure released. The reaction product was repeatedly washed with ethanol to remove residual PVP and organic products. After drying, ultrapure nano-copper powder was obtained.
[0041] Scanning electron microscope images of ultrapure nano copper powder are shown below. Figure 1 As shown, the nano-copper powder has a nearly spherical morphology and uniform size, approximately 90 nm. The laser particle size distribution results of the nano-copper powder are as follows: Figure 2 As shown, the average particle size is 89.3 nm. Figure 3As shown, the X-ray diffraction (XRD) pattern indicates that the nano-copper powder is composed of single-phase face-centered cubic copper. The purity of the obtained nano-copper powder was determined by glow discharge mass spectrometry (GD-MS). The content of other metals besides copper was found to be less than 30 ppm, and its metal-based purity (the mass percentage of copper in the nano-copper powder) was ≥99.997%.
[0042] Example 2
[0043] 0.1 g of copper octoate (5N purity) and 0.8 g of hexadecyltrimethylammonium bromide (5N purity) were placed in a 100 ml high-pressure vessel. 0.3 g of 3A molecular sieve was added, and formaldehyde (copper:formaldehyde molar ratio = 1:78.1) was introduced at 0.5 MPa. The partial pressure of carbon dioxide and the temperature were adjusted to 15 MPa and 60 °C, respectively. The mixture was stirred for 10 min. The temperature was then raised to 160 °C and reacted for 0.5 h. The pressure was then released, and the reaction product was repeatedly washed with ethanol and dried to obtain ultrapure nano-copper powder. Figure 4 As shown, the average particle size of the obtained nano-copper powder was measured to be 95.2 nm using a laser particle size analyzer.
[0044] Example 3
[0045] 0.1 g of copper oleate (5N purity) and 0.4 g of chitosan (4N purity, average molecular weight 30000 g / mol) were placed in a 100 ml high-pressure vessel. 0.2 g of 4A molecular sieve was added, and carbon monoxide (copper:carbon monoxide molar ratio = 1:56) was introduced at 0.2 MPa. The partial pressure of carbon dioxide and the temperature were adjusted to 12 MPa and 40 °C, respectively. The mixture was stirred for 30 min. The temperature was then raised to 160 °C and reacted for 4 h. Subsequently, the temperature was lowered and the pressure released. The reaction product was repeatedly washed with ethanol and dried to obtain ultrapure nano-copper powder. Figure 5 As shown, the average particle size of the obtained nano-copper powder was measured to be 68.3 nm using a laser particle size analyzer.
[0046] Example 4
[0047] 0.1 g of copper stearate (5N purity) and 0.8 g of polyvinylpyrrolidone (4N purity, average molecular weight 58000 g / mol) were placed in a 100 ml high-pressure vessel. 0.2 g of 3A molecular sieve was added, and hydrogen gas was introduced at 0.8 MPa (copper:hydrogen molar ratio = 1:225.2). The partial pressure of carbon dioxide and the temperature were adjusted to 8 MPa and 40 °C, respectively. The mixture was stirred for 60 min. The temperature was then raised to 220 °C and reacted for 1 h. The pressure was then released, and the reaction product was repeatedly washed with ethanol and dried to obtain ultrapure nano-copper powder. Figure 6 As shown, the average particle size of the obtained nano-copper powder was measured to be 28.7 nm using a laser particle size analyzer.
[0048] Comparative Example 1
[0049] Sodium di-(2-ethylhexyl)succinate sulfonate (3N purity) and copper chloride (5N purity) were dissolved in water to prepare solutions with concentrations of 0.02 mol / L and 0.2 mol / L, respectively. 1 ml of these solutions was placed in a 100 ml high-pressure vessel, and 0.3 g of polyvinylpyrrolidone (4N purity, average molecular weight 10000 g / mol) was added. The vessel was then filled with 0.8 MPa hydrogen gas (copper:hydrogen molar ratio = 1:178.6), and the partial pressure of carbon dioxide and temperature were adjusted to 10 MPa and 40 °C, respectively. The mixture was stirred for 60 min. The temperature was then raised to 180 °C and reacted for 2 h. Subsequently, the temperature was lowered and the pressure released. The reaction product was repeatedly washed with ethanol to remove residual PVP and organic products, and then dried to obtain nano-copper powder.
[0050] like Figure 7 As shown in the XRD pattern, the nano-copper powder consists of face-centered cubic copper and a small amount of cuprous oxide. Purity was determined using GD-MS. As shown in Table 1, the Na ion content was as high as 89.3 ppm, the total measurable impurity content was 181 ppm, and the copper powder metal-based purity was 99.98%. This indicates that the metal elements in the surfactant of the supercritical carbon dioxide microemulsion method have a significant impact on the purity of the synthesized nano-copper powder. Furthermore, the trace amounts of water generated in the container without a dehydrating agent can lead to copper powder oxidation. Comparative Example 1 used only one substance containing sodium ions; if a reducing agent such as sodium borohydride is used instead of a gaseous reducing agent, further metal impurities will be introduced.
[0051] Table 1. Elemental composition of the nano-copper powder obtained in Comparative Example 1
[0052] Element determination Test results / mg / kg Element determination Test results / mg / kg Element determination Test results / mg / kg Li <0.05 Ga <0.005 Nd <0.005 Be <0.05 Ge <0.05 Sm <0.005 B 0.13 As 0.35 Eu <0.005 C / Se 0.21 Gd <0.005 N / Br <0.005 Tb <0.005 O / Rb <0.005 Dy <0.005 F 0.2 Sr <0.005 Ho <0.005 Na 89.3 Y <0.005 Er <0.005 Mg 0.13 Zr <0.05 Tm <0.005 Al 0.2 Nb <0.05 Yb <0.005 Si 14.3 Mo 0.014 Iu <0.005 P 0.6 Ru <0.005 Hf <0.05 S 8.6 Rh <0.05 Ta <0.05 Cl 61.2 Pd 0.441 W <0.05 K 0.03 Ag 1.7 Re <0.005 Ca 0.35 Cd <0.005 Os <0.005 Sc <0.005 In <0.05 Ir <0.05 Ti 0.089 Sn 2.12 Pt <0.05 V 0.012 Sb <0.05 Au <0.005 Cr 0.11 Te <0.005 Hg <0.005 Mn 0.046 I <0.005 T1 0.05 Fe 0.07 Cs <0.005 Pb <0.005 Co 0.016 Ba <0.005 Bi <0.005 Ni 0.74 La <0.005 Th <0.005 Cu matrix Ce <0.005 U <0.005 Zn 0.32 Pr <0.005 H /
[0053] The above embodiments are merely illustrative of the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and substance defined by the claims of the present invention; and such modifications or substitutions are still within the scope defined by the claims of the present invention.
Claims
1. A method for preparing ultrapure nano copper powder by reducing an organic copper salt, characterized in that: The following steps are involved: (1) placing an organic copper salt and a morphology control agent in a container, adding a dehydrating agent, introducing a gas reducing agent, introducing carbon dioxide and adjusting the pressure and temperature of the carbon dioxide to make the carbon dioxide reach a supercritical state, stirring, and obtaining a mixture; (2) heating the mixture obtained in step (1) to react to obtain a reaction product, cooling and releasing the pressure, washing away excess morphology control agent and organic products, and drying to obtain ultrapure nano copper powder.
2. The method according to claim 1, characterized in that In step (1), the organic copper salt is one or more selected from fatty acid copper, copper cyclohexane acid, and copper oleate with a carbon chain length of 8 to 18 carbons; the purity of the organic copper salt is ≥5N.
3. The method according to claim 1, characterized in that In step (1), the morphology control agent is one or more selected from polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, and chitosan.
4. The method according to claim 1, characterized in that: In step (1), the mass ratio of the organic copper salt to the morphology control agent is 1:20-1:100, calculated on the basis of copper element.
5. The method according to claim 1, characterized in that In step (1), the dehydrating agent is one of 3A or 4A molecular sieves, preferably 3A molecular sieve.
6. The method according to claim 1, characterized in that In step (1), the mass ratio of the organic copper salt to the water removing agent is 1:5-1:20, calculated on the basis of copper element.
7. The method according to claim 1, characterized in that In step (1), the gas reducing agent is one or more selected from hydrogen, formaldehyde, and carbon monoxide, preferably hydrogen.
8. The method according to claim 1, characterized in that In step (1), the molar ratio of the organic copper salt to the gas reducing agent, calculated on the basis of copper element, is less than 1:
50.
9. The method according to claim 1, characterized in that: In step (2), the heating temperature is 160-220° C. and the reaction time is 0.5-4 hours.
10. The method according to claim 1, characterized in that The average particle size of the obtained ultrapure nano copper powder is less than 100nm, and the metal base purity is ≥99.997%.
Citation Information
Patent Citations
Method for preparing nano-copper
CN101890506A
Aqueous-phase preparation method for re-dispersible nano-copper particles
CN102371358A